Pigmentary Changes In Pregnancy - Neogi Bidisa Guha; Chattopadhyay S.P; Rajagopal A (Wolters Kluwer Medknow Publications, 1995)
Primary changes in one hundred pregnant females between 21 to 37 years were studied. Although 72% had hypermelanotic changes of some kind, only 20% of them were aware cosmetically; 56% of cases had chloasma. Incidence of centrofacial and malar type was 46.3% while mandibular types was seen in 7.1%. Hyperpigmentation was moderate in 70% and severe in 10% of cases and was more in multigravida than in primigravida. In primigravida , 90% had onset of chloasma in 2nd trimestar. Histopathological studies revealed increased melanins in both epidermis and dermis in 80% of severe type of chioasma (10 cases).